Malignant neuroectodermal tumor with melanocytic and rhabdomyoblastic differentiation - Brian P. Rubin; Munir R. Tanas (Rare Tumors, 2009)
Malignant melanoma can metastasize widely and vary significantly in its histological appearance; it rarely presents as a deep-seated mass without an obvious primary site elsewhere. Malignant peripheral nerve sheath tumor (MPNST) is a high-grade sarcoma characterized by conventional and epithelioid subtypes. MPNST can demonstrate heterologous differentiation, usually in the form of osteosarcomatous, chondrosarcomatous, or rhabdo-myosarcomatous differentiation. MPNST does not harbor true melanocytic differentiation, although epithelioid MPNST typically is diffusely S-100 protein positive and superficially can resemble malignant melanoma. An unusual intra-abdominal mass was recently encountered with features of both melanoma and conventional or epithelioid MPNST containing a fascicular spindle cell component, an epithelioid component with melanocytic differentiation, as well as a rhabdomyosarcomatous component. The terminology “malignant neuroectodermal tumor with melanocytic and rhabdomyoblastic differentiation” is proposed to describe this neoplasm, reflecting the unusual concomittant lines of differentiation as well as offering a possible rationale for nosologically challenging aspects of this neoplasm.